ANALISIS DIMENSI KUALITAS PELAYANAN PADA USAHA LAUNDRY UNTUK MENINGKATKAN KEPUASAN PELANGGAN: STUDI KASUS SAHABAT LAUNDRY COIN MEDAN - Febriana, Vinni; Juliana, Juliana; Rahmatillah, Riska; Akbar, Fatawil; Hayati, Fitri (Jurnal Bina Bangsa Ekonomika, 2025)
Service quality is one of the key factors in determining customer satisfaction, especially in service businesses such as laundry. This study aims to analyze the quality of services provided by Sahabat Laundry Coin and its impact on customer satisfaction. The research approach used is qualitative with data collection methods in the form of interviews, observations, and documentation. The analysis was carried out using five dimensions of service quality triggered by Parasuraman, namely reliability, responsiveness, assurance, empathy, and tangibles. The results of the study show that Sahabat Laundry Coin is able to provide good service by highlighting performance in completing work on time, quick response to complaints, and quality assurance through responsibility for mistakes that occur. Empathy and attention to the specific needs of customers are also a plus, supported by adequate physical facilities and professional employee performance. This research provides insight for laundry business actors in developing strategies to improve service quality to face increasingly fierce competition.